2021
DOI: 10.1038/s41598-021-96288-6
|View full text |Cite
|
Sign up to set email alerts
|

Single cell organization and cell cycle characterization of DNA stained multicellular tumor spheroids

Abstract: Multicellular tumor spheroids (MCTSs) can serve as in vitro models for solid tumors and have become widely used in basic cancer research and drug screening applications. The major challenges when studying MCTSs by optical microscopy are imaging and analysis due to light scattering within the 3-dimensional structure. Herein, we used an ultrasound-based MCTS culture platform, where A498 renal carcinoma MCTSs were cultured, DAPI stained, optically cleared and imaged, to connect nuclear segmentation to biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…To perform drug screening assays with 3D cell cultures, we used USW-assisted formation of tumor spheroids previously developed in our labs ( Christakou et al., 2015 ; Olofsson et al., 2018 , 2021 ; Vanherberghen et al., 2010 ; Wiklund et al., 2014 ). A498 renal carcinoma cells were seeded and exposed to ultrasound for 24 h, followed by 24 h of standard cell culture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To perform drug screening assays with 3D cell cultures, we used USW-assisted formation of tumor spheroids previously developed in our labs ( Christakou et al., 2015 ; Olofsson et al., 2018 , 2021 ; Vanherberghen et al., 2010 ; Wiklund et al., 2014 ). A498 renal carcinoma cells were seeded and exposed to ultrasound for 24 h, followed by 24 h of standard cell culture.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, paclitaxel-induced apoptosis was confined to the periphery of OVCAR8 spheroids ( Figure S3 G). Using image-analysis-based DNA content quantification, we have previously shown that cells in an active cell cycle stage are more common in the cell layers close to the spheroid surface ( Olofsson et al., 2021 ). Thus, it is possible that paclitaxel-induced apoptosis is preferentially observed in dividing cells in the periphery of the spheroids.…”
Section: Resultsmentioning
confidence: 99%
“…6d-f, centre). DAPI intensity differences [57][58][59] indicate temporal changes in the cell cycle at both the edge and centre (Fig. 6g-h, Supplementary figure 20a and SN2 Fig.…”
Section: Cell Fate Decisions Between Self-renewal and Differentiation...mentioning
confidence: 99%
“… 2 Since most cellular components are colorless, to observe for example the nuclei in MCTS, cells are usually stained with DNA binding fluorescent probes such as 4’,6-diamidino-2-phenylindole (DAPI) and observed through a fluorescence microscope. 3 Fluorescent staining of DNA by DAPI then allows to visualize of cell nuclei within 3D MCTS 4 to provide morphological information about the architecture of the MCTS. 5 …”
Section: Introductionmentioning
confidence: 99%